Discovery and characterization of benzyloxy piperidine based dopamine 4 receptor antagonists. (1st April 2022) - Tolentino, Kirsten T.; Mashinson, Viktoriya; Vadukoot, Anish K.; Hopkins, Corey R.
Graphical abstract: Abstract: The dopamine receptor 4 (D4 R) is highly expressed in both motor, associative and limbic subdivisions of the cortico-basal ganglia network. Due to the distribution in the brain, there is mounting evidence pointing to a role for the D4 R in the modulation of this network and its subsequent involvement in l -DOPA induced dyskinesias in Parkinson's disease. As part of our continued effort in the discovery of novel D4 R antagonists, we report the discovery and characterization of a new 3- or 4-benzyloxypiperidine scaffold as D4 R antagonists. We report several D4 R selective compounds (>30-fold vs. other dopamine receptor subtypes) with improved in vitro and in vivo stability over previously reported D4 R antagonists.